Young Children Use Probability to Infer Happiness and the Quality of Outcomes. (February 2020) - Doan, Tiffany; Friedman, Ori; Denison, Stephanie
Happiness with an outcome often depends on whether better or worse outcomes were initially more likely. In five experiments, we found that young children ( N = 620, Experiments 1–4) and adults ( N = 254, Experiment 5) used probability to infer emotions and assess outcome quality. In Experiments 1 and 2, 5- and 6-year-olds (but not 4-year-olds) inferred that an agent would be less happy with an outcome if a better outcome were initially more likely. In Experiment 3, 4- to 6-year-olds used probability to assess quality. These findings suggest a developmental lag between 4-year-olds' assessments of quality and happiness. We replicated this lag in Experiment 4. In Experiment 5, adults used probability to assess both quality and happiness. We suggest that children and adults may use probability to establish a standard against which actual outcomes are compared. Doing so might allow them to make probability-based inferences of happiness without drawing on counterfactual reasoning.